MENTAL ARITHMETIC IN ELEMENTARY SCHOOLS - Hakimova Marjona Iskandarzoda; Dots. Normo`minov Sherzod To`ychiyevich (Journals Park Publishing, 2024)
The widespread access to the free functioning of educational institutions in our country has also led to free competition in the education system. Of course, where there is competition, research, the desire for innovation, is evident, and as a result of these studies, high quality is achieved. (Matthew 24:14; 28:19, 20) Today, the introduction of new pedagogical technologies and methodologies in the preschool and primary education system is of great importance. Mental arithmetic is also an example of such new pedtechnology. This article summarizes the importance of mental arithmetic in the hierarchy of preschool and primary school-age children and the origin of mental arithmetic and abacus history.
Keywords: Mental arithmetic, abacus, soroban, mental capacity, brain right and left hemisphere development, mind and mind activity.